Structural optimization of composite fuselage panel including buckling and manufacturing constraints - Tanut Ungwattanapanit. (2013)
Multidisciplinary Design Optimization (MDO) techniques were successfully developed and applied in sizing a composite fuselage panel of narrow-body airliner. The detailed finite element fuselage panel was undergone optimization process developed around gradient-based optimizer MSC Nastran SOL 200. Coupling with selected critical loadings, all relevant sizing requirements including structural strength, stability, and basic manufacturing constraints were embedded into the optimization process. Semi-analytical, closed-form buckling constraints were also integrated inside the optimization algorithms so as to gain efficient optimization process suitable for getting close optimal results in the preliminary design phase.